Method for preparing a cotton stalk cellulose sponge substrate and applications thereof
Patent Information
- Application Number
- CN202410017119.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-05
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-01-05
AI Technical Summary
然而,在目前的棉秆研究中,棉秆基生物质多孔材料的研究报导较少,且其报导研究中,是将废弃棉秆粉碎进行提取纤维素,再通过进一步的溶解、分散、交联、冷冻干燥得到多孔材料,这种技术路线的设计,增加了多孔材料的制备步骤,使之变得过于复杂,同时大量使用化学试剂,使其在经济上加大了生产成本
[0012] Compared with the prior art, the technical effects of this invention are as follows: (1) The selected raw materials are inexpensive and readily available, and are waste cotton stalks. (2) Recycling and reusing waste cotton stalks has economic and environmental significance. (3) The cellulose sponge has no additives and is obtained directly from cotton stalks without grinding or cross-linking, which has the advantages of simple and economical preparation process. (4) By scaling up the experiment by 20 times, a cellulose sponge with good anisotropy can still be obtained. (5) The cellulose sponge retains the anisotropic and continuous three-dimensional network structure of cotton stalks, and has the advantages of light weight, high porosity, and special pore structure. It is a support for many materials and has a wide range of applications. (6) The cellulose sponge has superhydrophilic/underwater superoleophobic properties, and its oil contact angle in water is greater than 150°. o Furthermore, when the sponge absorbs oil and is placed in water, the oil will automatically precipitate out of the cellulose sponge, exhibiting good underwater oleophobic properties and circulation performance. (7) The special pore structure and compressibility of the pore structure of the cellulose sponge endow it with good emulsion separation performance, with separation efficiencies of over 99% for both water-in-oil emulsions and oil-in-water emulsions. (8) The cellulose sponge has good removal effects on methylene blue and Congo red, with removal rates of over 99% and 97%, respectively.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of design and R&D technology of environmentally friendly material preparation methods. Specifically, it discloses a method for preparing cotton stalk cellulose sponge substrate and its application. It is mainly aimed at making reasonable use of waste cotton stalks in Xinjiang, turning waste into treasure. The prepared cellulose sponge substrate is applied in the field of oil-water separation. Background Technology
[0002] Porous materials, with their interconnected network structure, possess advantages such as low relative density, high specific strength, high specific surface area, light weight, and good permeability. They are a popular platform and substrate candidate for multifunctional composite materials, widely used in building insulation, wastewater filters, adsorbents, drug delivery, power storage devices, and photocatalysts. However, these porous materials also suffer from drawbacks such as expensive raw materials, complex preparation processes, non-renewability, poor compressibility, and limited functionality, restricting their large-scale application. Therefore, developing environmentally friendly, renewable, and multifunctional porous materials is a new trend in "deepening the battle against pollution" and responding to the sustainable development strategy. Xinjiang is a cotton-growing region, generating a large amount of cotton stalk waste annually. The main components of cotton stalks are cellulose (approximately 36%), hemicellulose (approximately 21%), and lignin (approximately 28%). Therefore, research on how to effectively recycle and utilize cotton stalks has been extensively conducted. In recent years, many researchers have successfully extracted cellulose and cellulose nanofibers from waste cotton stalks through recycling, and then blended the extracted cellulose with other materials to prepare composite materials. This approach not only effectively utilizes cotton stalk waste but also produces novel, environmentally friendly, and low-cost biomass composite materials with controllable performance, demonstrating significant research and practical potential. However, current research on cotton stalk-based biomass porous materials is limited, and existing reports typically involve crushing waste cotton stalks to extract cellulose, followed by further dissolution, dispersion, cross-linking, and freeze-drying to obtain porous materials. This technical route increases the complexity of porous material preparation by adding numerous steps and significantly raises production costs due to the extensive use of chemical reagents. Directly removing lignin and hemicellulose from cotton stalks without cross-linking polymerization to obtain cellulose sponge materials has substantial research and production value. Therefore, in the context of today's sustainable development strategy and the "dual carbon" environment, developing simple and convenient technologies for efficiently recycling and utilizing waste cotton stalks to prepare cellulose sponges is crucial for waste recycling and resource utilization. Summary of the Invention
[0003] To achieve the above objectives, this invention provides a method for preparing cotton stalk-based cellulose sponge. Using waste cotton stalks as raw material, a chemical treatment method is employed to directly remove lignin and hemicellulose from the cotton stalks, yielding a sponge material containing a large amount of cellulose. This method has advantages such as inexpensive and readily available raw materials, a simple preparation method, high porosity of the cotton stalk cellulose sponge material, additive-free sponge material that can be used as a support for various materials, and the ability to effectively recycle and utilize waste cotton stalks, enabling large-scale production and easy scaling up.
[0004] The technical solution of the present invention is as follows: I. A method for preparing cotton stalk cellulose sponge substrate, the preparation method comprising the following steps: (I) Peeling waste cotton stalks, cutting them into 0.5cm segments, washing them with deionized water, and drying them in an oven at 110℃ for 5h to obtain absolutely dry cotton stalks for later use; (II) Taking 3g of the absolutely dry cotton stalks prepared in step (1) and placing them in a conical flask containing 100ml of deionized water, adding 4ml of acid solution to the conical flask, steaming them in an oven at 110℃ for 4-8h, rinsing them with deionized water, and freeze-drying them to obtain acid-treated cotton stalks for later use; (III) Placing the acid-treated cotton stalks obtained in step (2) into 100ml of a solution with a concentration of 3-15wt% NaOH, steaming them in an oven at 110℃ for 4-8h, washing them with deionized water, and freeze-drying them to obtain alkali-treated cotton stalks for later use; (IV) Placing the alkali-treated cotton stalks obtained in step (3) into a 100ml solution containing 1wt% NaOH at a pH of 4-5. The NaClO2-acetic acid solution is placed in a water bath at 70-80℃ and heated for bleaching for 18 hours. The NaClO2-acetic acid solution is replaced every 6 hours. After cooling, it is rinsed with deionized water until neutral and then freeze-dried to obtain cotton stalk cellulose sponge substrate.
[0005] Furthermore, the acid solution is nitric acid, sulfuric acid, or glacial acetic acid.
[0006] Furthermore, the cooking time in step (2) is preferably 4 hours.
[0007] Furthermore, the concentration of NaOH in step (3) is preferably 12 wt% or 9 wt%.
[0008] Furthermore, the cooking time in step (3) is preferably 4 hours.
[0009] Furthermore, the water bath temperature in step (4) is preferably 75°C.
[0010] Furthermore, in step (4), the pH value is preferably 4.6.
[0011] II. The prepared cotton stalk cellulose sponge substrate is used in emulsion separation and dye removal applications, wherein the selected oil is one or more of the following: n-hexane, n-heptane, petroleum ether, dichloromethane, silicone oil, carbon tetrachloride, pump oil, and mineral oil; the selected surfactants are Span 80 and Tween 60; and the selected dyes are methylene blue and Congo red.
[0012] Compared with the prior art, the technical effects of this invention are as follows: (1) The selected raw materials are inexpensive and readily available, and are waste cotton stalks. (2) Recycling and reusing waste cotton stalks has economic and environmental significance. (3) The cellulose sponge has no additives and is obtained directly from cotton stalks without grinding or cross-linking, which has the advantages of simple and economical preparation process. (4) By scaling up the experiment by 20 times, a cellulose sponge with good anisotropy can still be obtained. (5) The cellulose sponge retains the anisotropic and continuous three-dimensional network structure of cotton stalks, and has the advantages of light weight, high porosity, and special pore structure. It is a support for many materials and has a wide range of applications. (6) The cellulose sponge has superhydrophilic / underwater superoleophobic properties, and its oil contact angle in water is greater than 150°. o Furthermore, when the sponge absorbs oil and is placed in water, the oil will automatically precipitate out of the cellulose sponge, exhibiting good underwater oleophobic properties and circulation performance. (7) The special pore structure and compressibility of the pore structure of the cellulose sponge endow it with good emulsion separation performance, with separation efficiencies of over 99% for both water-in-oil emulsions and oil-in-water emulsions. (8) The cellulose sponge has good removal effects on methylene blue and Congo red, with removal rates of over 99% and 97%, respectively. Attached Figure Description
[0013] Appendix Figure 1 Here are SEM images of the cotton stalk's (a) cross-section and (b) longitudinal section; (Attached) Figure 2 Here are SEM images of the cellulose sponge material: (a) cross-section and (b) longitudinal section; (Attached) Figure 3 This is a diagram showing the water contact angle of a cellulose sponge in air; attached. Figure 4 (a) A wetted photograph of dichloromethane underwater; (b) A wetted photograph of n-hexane underwater; (c) A dynamic diagram of water adsorption in n-hexane; (d) A dynamic diagram of adsorption-desorption of n-hexane; (e) A dynamic diagram of adsorption-desorption of dichloromethane; (Attached) Figure 5 (a) is the separation apparatus; (b) are the UV spectra of methylene blue dye before and after separation; (c) are the UV spectra of Congo red dye before and after separation; (Attached) Figure 6 These are optical photographs of the solutions in the cellulose sponge emulsion before and after separation, where (a) is a water-in-oil emulsion and (b) is an oil-in-water emulsion. Detailed Implementation
[0014] The technical solution of the present invention will be further described below with reference to the embodiments and accompanying drawings.
[0015] Example 1. A method for preparing a cotton stalk cellulose sponge substrate: (1) Peel waste cotton stalks, cut them into 0.5cm thick slices, wash them with deionized water, and dry them in an oven at 110℃ for 5 hours to obtain absolutely dry cotton stalks; (2) Weigh 3g of absolutely dry cotton stalks into a conical flask containing 100ml of deionized water, add 4ml of sulfuric acid to the conical flask, and boil it in an oven at 110℃ for 4 hours, then rinse it with a large amount of deionized water; (3) Then put the product into 100ml of 12wt% NaOH solution, boil it in an oven at 110℃ for 4 hours, and then wash it with a large amount of deionized water; (4) Finally, put the above product into 100ml of a solution containing 1wt% NaOH at a pH of about 4.6. In a NaClO2-acetic acid solution, the mixture was heated at 75°C for 18 hours, with the NaClO2-acetic acid solution being replaced every 6 hours. After cooling with ice water, it was rinsed with a large amount of deionized water until neutral, and then freeze-dried to obtain a sulfuric acid-pretreated cotton stalk cellulose sponge substrate. Figure 1 The SEM image of the cotton stalks used in this invention reveals that the cotton stalks have a good pore structure with anisotropy, and the pores contain numerous small spherical substances. The compositional analysis of the cotton stalks is listed in Table 1. Table 1 shows that cellulose is the most abundant component of the cotton stalks, and the xylem content is slightly higher than that of the core. To obtain a better sponge structure, this invention selects the xylem of the cotton stalks as the research object. Figure 2 This is an electron microscope image of the cellulose sponge material from Example 1 of the present invention. Figure 2 It can be seen that the cellulose sponge material is relatively white in color, retaining the unique anisotropic pore structure of the cotton stalk, and the small spherical material within the pores has been removed. Referring to Table 2, the lignin content in the cotton stalk cellulose sponge substrate obtained in Example 1 is <0.05%, which can be assumed that the lignin in the sponge material has been completely removed. Meanwhile, the cellulose content in the sponge material is relatively high, with a yield of approximately 31%. This result is quite close to the cellulose content in cotton stalks. Furthermore, a 20x magnification experiment with all raw materials also yielded a cellulose sponge with the same pore structure. These experimental results and data confirm the potential for large-scale industrial production.
[0016] Table 1 Content of various components in cotton stalks
[0017] xylem 73.49 53.39 24.37 1.49 1.56 Core 70.74 50.35 20.05 1.41 3.07
[0018] Table 2. Content and yield of each component in cellulose sponge
[0019] 92.05 82.37 <0.05 31.39
[0020] Example 2: The cotton stalk cellulose sponge substrate prepared in Example 1 was put into practical application. (1) Wettability test, the results are as follows: Figure 3 , Figure 4 As shown. Figure 3 This is a diagram showing the water contact angle of cotton stalk cellulose sponge substrate in air. As can be seen from the diagram, water droplets are quickly absorbed upon contact with the surface of the cotton stalk cellulose sponge substrate, indicating that the substrate has superhydrophilicity, with a water contact angle of 0°. o (2) Figure 4 a and Figure 4 b are optical photographs of cotton stalk cellulose sponge substrate in water, dichloromethane, and n-hexane, respectively. As shown in the figure, the cotton stalk cellulose sponge substrate has excellent underwater superoleophobicity. Oil droplets of n-hexane and dichloromethane can remain intact on the surface of the cotton stalk cellulose sponge substrate or slide off completely. (3) The cotton stalk cellulose sponge substrate also has underwater hydrophilicity. In n-hexane, water can be well absorbed by the cotton stalk cellulose sponge substrate, such as Figure 4 As shown in Figure c, this indicates that the cotton stalk cellulose sponge substrate has higher hydrophilicity than its oleophilicity. Furthermore, it will adsorb dichloromethane, such as... Figure 4 As shown in d, or n-hexane, such as Figure 4 When the cotton stalk cellulose sponge substrate shown in e is placed in water, it can be observed that both hexane and dichloromethane can precipitate from the cotton stalk cellulose sponge substrate. This also indicates that the prepared cotton stalk cellulose sponge substrate has superhydrophilicity, underwater superoleophobicity, and oil-water separation properties. (4) Place the cotton stalk cellulose sponge substrate in a self-built filter device, such as Figure 5 As shown in Figure a, methylene blue aqueous solution and Congo red aqueous solution were poured into the device, respectively. The device was allowed to filter automatically. The absorbance of the dye before and after filtration was measured using a UV-Vis spectrophotometer. The results were then converted to concentration using a standard curve, and the removal efficiency was calculated using the formula below.
[0021]
[0022] like Figure 5 b and 5c show that after separation, the staining of methylene blue and Congo red became lighter and the color was close to colorless. At the same time, the spectra after separation also disappeared, and the absorbance was around 0. This indicates that the cotton stalk cellulose sponge substrate has a good retention rate for methylene blue and Congo red, and its removal efficiency for methylene blue and Congo red is above 99% and 97%, respectively. (5) Using the same separation device, the cotton stalk cellulose sponge substrate was placed in it, and the pre-prepared emulsions (oil-in-water and water-in-oil) were poured into it, and the separated solutions were collected. The experiment found that the separated water-in-oil emulsion and oil-in-water emulsion changed from the milky white of the raw materials to colorless and transparent. And when observed with an optical microscope, no small spherical substances were observed in the separated emulsions. This indicates that the cotton stalk cellulose sponge substrate has a good emulsion separation efficiency. This phenomenon is related to the superhydrophilicity of the cotton stalk cellulose sponge substrate.
[0023] Example 3: A method for preparing a cotton stalk cellulose sponge substrate, (1) peeling waste cotton stalks, cutting them into 0.5cm thick pieces, washing them with deionized water, and drying them in an oven at 110℃ for 5h to obtain absolutely dry cotton stalks; (2) weighing 3g of absolutely dry cotton stalks into a conical flask containing 100ml of deionized water, adding 4ml of nitric acid to the conical flask, steaming it in an oven at 110℃ for 4h, and then rinsing it with a large amount of deionized water; (3) then placing the product into a 100ml (3) The product was boiled in a 9wt% NaOH solution in an oven at 110°C for 4 hours and then washed with a large amount of deionized water. (4) Finally, the product was placed in 100ml of NaClO2-acetic acid solution containing 1wt% NaClO2 at a pH of about 4.6 and heated at 75°C for 18 hours. The NaClO2-acetic acid solution was replaced every 6 hours. After cooling with ice water, the product was rinsed with a large amount of deionized water until neutral and then freeze-dried to obtain cotton stalk cellulose sponge substrate.
[0024] Example 4: A method for preparing a cotton stalk cellulose sponge substrate, (1) peeling waste cotton stalks, cutting them into 0.5cm thick pieces, washing them with deionized water, and drying them in an oven at 110℃ for 5h to obtain absolutely dry cotton stalks; (2) weighing 3g of absolutely dry cotton stalks into a conical flask containing 100ml of deionized water, adding 4ml of sulfuric acid to the conical flask, steaming it in an oven at 110℃ for 4h, and then rinsing it with a large amount of deionized water; (3) then placing the product into a 100ml (3) The product was boiled in a 9wt% NaOH solution in an oven at 110°C for 4 hours and then washed with a large amount of deionized water. (4) Finally, the product was placed in 100ml of NaClO2-acetic acid solution containing 1wt% NaClO2 at a pH of about 4.6 and heated at 75°C for 12 hours. The NaClO2-acetic acid solution was replaced every 6 hours. After cooling with ice water, the product was rinsed with a large amount of deionized water until neutral and then freeze-dried to obtain cotton stalk cellulose sponge substrate.
Claims
1. A method for preparing a cotton stalk cellulose sponge substrate, characterized in that, The preparation method includes the following steps: (a) Peel the waste cotton stalks, cut them into 0.5cm sections, wash them with deionized water, and dry them in an oven at 110℃ for 5 hours to obtain absolutely dry cotton stalks for later use. (ii) Take 3g of the oven-dried cotton stalks prepared in step (1) and place them in a conical flask containing 100ml of deionized water. Add 4ml of acid solution to the conical flask and place it in an oven at 110℃ for 4-8 hours. After rinsing with deionized water, freeze-dry the cotton stalks to obtain the acid-treated cotton stalks for later use. (iii) Place the acid-treated cotton stalks obtained in step (2) into 100ml of a 3-15wt% NaOH solution, boil them in an oven at 110℃ for 4-8h, wash them with deionized water, and freeze-dry them to obtain alkali-treated cotton stalks for later use. (iv) Place the alkali-treated cotton stalks obtained in step (3) into 100ml of NaClO2-acetic acid solution containing 1wt% NaClO2 at pH 4-5, place it in a water bath at 70-80℃, heat and bleach for 18h, during which the NaClO2-acetic acid solution is replaced every 6h, after cooling, rinse with deionized water until neutral, freeze dry, and the cotton stalk cellulose sponge substrate can be obtained.
2. The method for preparing a cotton stalk cellulose sponge substrate according to claim 1, characterized in that, The acid solution is nitric acid, sulfuric acid, or glacial acetic acid.
3. The method for preparing a cotton stalk cellulose sponge substrate according to claim 1, characterized in that, The steaming time in step (2) is 4 hours.
4. The method for preparing a cotton stalk cellulose sponge substrate according to claim 1, characterized in that, The concentration of NaOH in step (3) is 12 wt% or 9 wt%.
5. The method for preparing a cotton stalk cellulose sponge substrate according to claim 1, characterized in that, The steaming time in step (3) is 4 hours.
6. The method for preparing a cotton stalk cellulose sponge substrate according to claim 1, characterized in that, The water bath temperature in step (4) is 75°C.
7. The method for preparing a cotton stalk cellulose sponge substrate according to claim 1, characterized in that, The pH value in step (4) is 4.
6.
8. The cotton stalk cellulose sponge substrate prepared according to claim 1 is used in emulsion separation and dye removal applications, wherein the oil in the emulsion is one or more of hexane, heptane, petroleum ether, dichloromethane, silicone oil, carbon tetrachloride and mineral oil; the surfactant in the emulsion is Span 80 and Tween 60, and the selected dye is methylene blue and Congo red.
Citation Information
Patent Citations
Nanocellulose-based filter membrane as well as preparation method and application thereof
CN116078184A